2010
DOI: 10.1051/0004-6361/201014533
|View full text |Cite
|
Sign up to set email alerts
|

TheHerschelVirgo Cluster Survey

Abstract: Passive early-type galaxies (ETGs) provide an ideal laboratory for studying the interplay between dust formation around evolved stars and its subsequent destruction in a hot gas. Using Spitzer-IRS and Herschel data we compare the dust production rate in the envelopes of evolved AGB stars with a constraint on the total dust mass. Early-type galaxies which appear to be truly passively evolving are not detected by Herschel. We thus derive a distance independent upper limit to the dust grain survival time in the h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 35 publications
8
44
0
Order By: Relevance
“…A similarly low value of the time-scale of interstellar dust destruction, only 46 Myr, is derived for early type galaxies (ETGs) detected in FIR by Spitzer observations (Clemens et al 2010). For a comparison, we also ran calculations of the SSP evolution with a longer dust destruction time-scale of 1 Gyr which corresponds to a lower gas density of 10 −4 cm −3 .…”
Section: The Origin Of Dust In Red-ementioning
confidence: 75%
“…A similarly low value of the time-scale of interstellar dust destruction, only 46 Myr, is derived for early type galaxies (ETGs) detected in FIR by Spitzer observations (Clemens et al 2010). For a comparison, we also ran calculations of the SSP evolution with a longer dust destruction time-scale of 1 Gyr which corresponds to a lower gas density of 10 −4 cm −3 .…”
Section: The Origin Of Dust In Red-ementioning
confidence: 75%
“…At the low dust-mass end, at least several early-type galaxies (three elliptical and three S0) with M B ∼ −18 to −20 are undetected in the Herschel Space Observatory survey of the Virgo cluster. Upper limits constrain the associate dust mass of these galaxies to be <10 4 M (Clemens et al 2010). For comparison, the Virgo cluster spiral galaxies in the same B-band luminosity range also observed by Herschel have dust masses of ∼10 7 − 10 8 M (Davies et al 2011).…”
Section: Dust In Early-type Sn Ia Hostsmentioning
confidence: 78%
“…In fact, since the effects of dust and age show different redshift evolution (see Figure 10), the amount of dust required in such a scenario would need to be fine-tuned to the specific cluster redshift. Furthermore, the typical timescale for dust destruction, ∼10 7 -10 8 yr (Jones et al 1996;Temi et al 2007;Clemens et al 2010), is significantly shorter than the typical ages of even the youngest z ∼ 1.2 red-sequence ellipticals (∼10 9 yr; Rettura et al 2010), so we do not expect a difference in dust between blue and red extremes of the red sequence to play a role in the CMR residual scatter. Finally, a dust distribution in which each galaxy is reddened the same amount is a similarly unlikely fine-tuning scenario, and is inconsistent with findings in nearby ellipticals, in which infrared-inferred dust masses vary by several orders of magnitude (Tran et al 2001;Temi et al 2004Temi et al , 2007.…”
Section: Red-sequence Scattermentioning
confidence: 81%
“…We detected only the silicon features at about 10 and 18 μm, arising from the circumstellar envelopes of O-rich AGB stars. This dust, once diffused in the ISM, it is destroyed by the hot gas halo (see Clemens et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Bressan et al (2006) showed that the MIR spectra of the majority of the massive ETGs in clusters show neither Polycyclic Aromatic Hydrocarbons (PAHs) features nor emission lines, and exhibit only the broad silicate emission feature around 10 μm arising from circumstellar dust around oxygen-rich AGB stars, superimposed on a stellar photospheric continuum. ETGs with such MIR spectra, with either un-excited, or likely absent (see Clemens et al 2010), ISM, represent the class of passively evolving ETGs and can be considered the fossil record of galaxy evolution.…”
Section: Introductionmentioning
confidence: 99%